Collaboration via co-authorship trends in Government of Canada forestry research - Heather MacDonald; Daniel W. McKenney; Kaitlin DeBoer (The Forestry Chronicle)
As part of its long history, the Canadian Forest Service (CFS) has a mandate to collaborate and share its scientific research. Publishing peer-reviewed scientific literature is an important part of this process. Using a database of CFS publications over the past fifty years, we highlight the continuing publication record of this sector of the Canadian government. The average number of authors reported in the CFS bookstore increased from 1.4 authors per article in the 1960s and 1.5 in the 1970s to just under five authors per publication from 2010 to 2018. Our work also illustrates challenges with longitudinal analysis of citation databases. In particular, use of a popular citation database resulted in significantly fewer articles authored by one person, and significantly more articles with twenty or more authors compared to the publicly available CFS “bookstore” of publications. Based on our findings, we outline a number of recommendations for use of citation data to inform collaboration research.